Assessment of the Current State and Prospects for the Development of the Digital Economy of the Republic of Azerbaijan - ABDULLAYEV, Kamran; BADALOVA, Sevda; MUSTAFAYEV, Asif; ZEYNALOV, Mahir; BABAYEVA, Aynur (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
Azerbaijan, along with other advanced countries in the world, is currently characterised by the intensive development of digital economies. That is why the issue of the main directions of development of the information and technology environment in the Azerbaijani economy is relevant. The research aims to study and summarise aspects of the current state and peculiarities of the development of the digital economy of Azerbaijan. The study used the induction, deduction, analysis, systematisation, SWOT analysis methods. Azerbaijan is a fairly developed industrial and agricultural country, but the country’s economic environment is unstable. The development of the digital economy is negatively affected by a decrease in funding and a decline in the production of high-tech goods. However, the biggest problem is the low level of digital literacy of the population. Accordingly, the main directions for the development of digitalisation of economic processes in Azerbaijan should be measures to expand education in the field of information and computer technologies with the involvement of foreign specialists and introduce mandatory courses to improve the skills of digital specialists. The main factors in the development of Azerbaijan’s digital economy are foreign investment and human capital. Thus, the practical significance of the study is that the main established directions of formation of the digital economy in Azerbaijan can be used in further works of scientists to improve digitalisation in the country, and the established main educational direction can be used by the Azerbaijani authorities to bring the country to the world level following digital technologies.